Alternative splicing in prostate cancer. Issue 11 (November 2018) - Paschalis, Alec; Sharp, Adam; Welti, Jonathan; Neeb, Antje; Raj, Ganesh; Luo, Jun; Plymate, Stephen; Bono, Johann.
Abstract Androgen receptor (AR) splice variants (AR-Vs) have been implicated in the development and progression of metastatic prostate cancer. AR-Vs are truncated isoforms of the AR, a subset of which lack a ligand-binding domain and remain constitutively active in the absence of circulating androgens, thus promoting cancer cell proliferation. Consequently, AR-Vs have been proposed to contribute not only to resistance to anti-androgen therapies but also to resistance to radiotherapy in patients receiving combination therapy by promoting DNA repair. AR-Vs, such as AR-V7, have been associated with unfavourable clinical outcomes in patients; however, attempts to specifically inhibit or prevent the formation of AR-Vs have, to date, been unsuccessful. Thus, novel therapeutic strategies are desperately needed to address the oncogenic effects of AR-Vs, which can drive lethal forms of prostate cancer. Disruption of alternative splicing through modulation of the spliceosome is one such potential therapeutic avenue; however, our understanding of the biology of the spliceosome and how it contributes to prostate cancer remains incomplete, as reflected in the dearth of spliceosome-targeted therapeutic agents. In this Review, the authors outline the current understanding of the role of the spliceosome in the progression of prostate cancer and explore the therapeutic utility of manipulating alternative splicing to improve patient care. Androgen receptor (AR) splice variants (AR-Vs) are truncated isoforms of the AR, of which a subset remain constitutively active in the absence of circulating androgens. AR-Vs have been proposed to contribute to therapeutic resistance. The authors of this Review outline the current understanding of the role of the spliceosome in prostate cancer progression and explore the therapeutic utility of manipulating alternative splicing. Key points Persistent androgen receptor (AR) signalling is fundamental for the development of treatment resistance in prostate cancer and for its progression to lethal castration-resistant prostate cancer (CRPC). Truncated AR splice variants that lack the AR ligand-binding domain (LBD) and remain constitutively active in the absence of androgen ligands are a biologically credible mechanism of treatment resistance in CRPC. These splice variants occur through the process of alternative splicing, which is regulated by the spliceosome. AR splice variant 7 (AR-V7) is the most widely studied AR splice variant and has been associated with both an increased risk of biochemical relapse and inferior overall survival outcomes. Efforts to directly target AR splice variants have proved challenging owing to the loss of the LBD (the target of the currently approved anti-androgen therapies) and the intrinsically disordered nature of the AR amino-terminal domain. Targeting spliceosomal activity to inhibit the generation of AR splice variants represents an attractive alternative therapeutic strategy; however, the complexity of the spliceosome, and a lack of understanding of its biology, has resulted in a paucity of such agents being developed. Further research is urgently required to improve understanding of the splicing abnormalities that contribute to the progression of CRPC, as well as the consequences of inhibiting these factors, before the true utility of these therapies can be realized.